(untitled) (Physical Culture and Sport: Scientific Perspective, 2023)
Based on the analysis of the publications of leading Chinese scientists, educational programs of Chinese higher education institutions, and the regulatory framework of the PRC, it was found out that in recent years there has been a need for modernized training of future teachers of music, rethinking the developmental and educational possibilities of musical art; it was established that the training of a future music teacher in the People’s Republic of China takes place at several levels: preliminary education (receiving a specialty), bachelor, master, doctor; highlighted that in order to ensure the development of higher education, implement the strategy of restarting and renewing the country, and promoting the construction of a socialist and spiritual society, the "Law on Higher Education" was published in 2015; it was established that an important role in reforming the process of training future teachers of music was played by the "Guideline program of the bachelor’s study program of the specialty "Music", "National instructions for the training of music teachers for compulsory undergraduate courses", "National quality standards for teaching undergraduate majors in institutions of higher education", in accordance with which modern training of future music-pedagogical workers takes place; it was determined that the modern training of a future teacher of music is provided by an optimal combination of classroom and extra-class training of applicants, the choice of forms (lecture, practical and individual classes), the use of traditional and innovative teaching methods, modern teaching tools, the content of mandatory courses, optional disciplines, a large number of electives, which contributes to the quality training of teachers - musicians; it was found out that under conditions of thorough training, the future teacher of music will clearly understand the needs of children and the developmental and educational possibilities of musical art, it will be able to implement this in practice in the most optimal way, that is why such a teacher, who coming to school, will conduct lessons in an interesting, dynamic and cognitively.